N-type thermoelectric AgBiPbS₃ with nanoprecipitates and low thermal conductivity - Dong, Jinfeng (2024)
Thermoelectric sulfide materials are of particular interest due to the earth-abundant and cost-effective nature of sulfur. Here, we report a new n-type degenerate semiconductor sulfide, AgBiPbS3, which adopts a Fm3̅m structure with a narrow band gap of ∼0.32 eV. Despite the homogeneous distribution of elements at the scale of micrometer, Ag2S nanoprecipitates with dimensions of several nanometers were detected throughout the matrix. AgBiPbS3 exhibits a low room-temperature lattice thermal conductivity of 0.88 W m-1 K-1, owing to the intrinsic low lattice thermal conductivity of Ag2S and the effective scattering of phonons at nanoprecipitate boundaries. Moreover, compared to AgBiS2, AgBiPbS3 demonstrates a significantly improved weighted mobility of >16 cm2 V-1 s-1 at 300 K, leading to an enhanced PF of 1.6 μW cm-1 K-2 at 300 K. The superior electrical transport in AgBiPbS3 can be attributed to the high valley degeneracy of the L point (the conduction band minimum), which is contributed by the Pb s and Pb p orbitals. Further, Ga doping is found to be effective in modulating the Fermi levels of AgBiPbS3, leading to further enhancement of PF with a PFave of 2.7 μW cm-1 K-2 in the temperature range of 300-823 K. Consequently, a relatively high ZTave of 0.22 and a peak ZT of ∼0.4 at 823 K have been achieved in 3% Ga-doped AgBiPbS3, highlighting the potential of AgBiPbS3 as an n-type thermoelectric sulfide.